Development of a novel rapid non-invasive screening test for coeliac disease. Issue 5 (1st November 2000) - Baldas, V; Tommasini, A; Trevisiol, C; Berti, I; Fasano, A; Sblattero, D; Bradbury, A; Marzari, R; Barillari, G; Ventura, A; Not, T
Abstract : BACKGROUND: Coeliac disease is one of the commonest underdiagnosed diseases in general practice. The autoantigen recognised by the sera of patients with coeliac disease has recently been identified as tissue transglutaminase. AIMS: We evaluated a simple non-invasive immunological dot blot assay for coeliac disease, suitable for use by the general physician in the ambulatory setting. The sensitivity and specificity of this dot blot assay based on recognition of recombinant human transglutaminase were compared with those of antiendomysial antibodies and an enzyme linked immunosorbent assay. METHODS: Serum samples were analysed from 64 healthy controls, 58 first degree relatives of coeliacs, 74 diseased controls, and 70 biopsy confirmed untreated patients with coeliac disease. Dot blot assay and enzyme linked immunosorbent assay were performed using recombinant human transglutaminase as antigen. RESULTS: The dot blot assay, which can be performed in 20 minutes, was positive in all 70 untreated coeliacs (sensitivity 100%). Among the three control groups, there were three false positive tests by dot blot (specificity 98%), all belonging to the group of healthy subjects. The antiendomysial antibodies test missed five untreated coeliac patients (sensitivity 93%) and was negative in all three control groups (specificity 100%). The specificity of the immunosorbent assay was 99% for IgA and 98% for IgG, while sensitivity was 93% for IgA, 47% for IgG, and 100% for IgA and IgG combined. CONCLUSIONS: The dot blot assay is highly accurate in detecting untreated subjects with coeliac disease and can be performed in the general physician's medical office during the course of a routine examination. This innovative test is a practical, reliable alternative to both the immunofluorescent based antiendomysial test and immunosorbent assay for detection of transglutaminase antibodies for the diagnosis of coeliac disease.